The different effects of structurally related sulfakinins on Drosophila melanogaster odor preference and locomotion suggest involvement of distinct mechanisms. - Nichols, R.; Egle, J.P.; Langan, N.R.; Palmer, G.C. (Peptides, 2008)
Sulfakinins are myoactive peptides and antifeedant factors. Naturally occurring drosulfakinin I (DSK I; FDDYGHMRFNH(2)) and drosulfakinin II (DSK II; GGDDQFDDYGHMRFNH(2)) contain sulfated or nonsulfated tyrosine. We discovered sDSK II and nsDSK II influenced Drosophila melanogaster larval odor preference. However, sDSK I, nsDSK I, MRFNH(2), and saline did not influence odor preference. We discovered sDSK I and nsDSK I influenced larval locomotion. However, sDSK II, nsDSK II, MRFNH(2), and saline did not influence locomotion. Our novel data suggest distinct mechanisms underlie the effects of DSK I and DSK II peptides on odor preference and locomotion, parameters important to many facets of animal survival.